Penggunaan Problem Based Learning Pada Mata Pelajaran Dasar Kompetensi Kejuruan Teknik Mesin - Sukrawan, Yusep; Komaro, Mumu (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2011)
Basic Competency in Vocational subjects in Mechanical Engineering, vocational students have always faced the problems associated with engineering science to be done to establish the expected curriculum vocational competence. One solution that is considered suitable to solve the problem is the application of problem based learning, problem-solving method based discussion group. With the implementation of the model is expected to improve learning outcomes and student activities. The research method is a method of Classroom Action Research. The results showed that the application of problem based learning-based discussion group can improve student learning outcomes in the cognitive domain of the N-Gain 0.71 in the high category. The average value of 82.12 in the affective domain of the positive category and the average value of 90.9 in the psychomotor domain of very good category, while the average value of student activities at the low category.